A Decentral Theory of Governance: with the introduction of Bob Jessop - Bevir, Mark (Journal of Public Governance, 2009)
There are two leading narratives of governance. The first is a neoliberal discourse of markets, inspired by the idea of rational choice. The other is a story of networks, associated with institutionalism in political science. This paper argues that both rational choice and institutionalism rely on assumptions about our ability to deduce people’s beliefs from objective social facts about them, and yet that these assumptions are untenable given the philosophical critique of positivism. Hence, we need to modify our leading theories and narratives of governance. We need to decenter them. The paper explores the distinctive answers a decentered theory of governance would give to questions such as: Is governance new? Is governance a vague metaphor? Is governance uniform? How does governance change? Is governance’s failure inevitable? Finally, the paper explores some of the consequences of a decentered theory regarding our way of thinking about policy formation and democracy.